(untitled) - Spae, Joseph J. (Tokyo, 1972)
This book presents, for the first time, a collection of ancient Japanese Shinto prayers in a format where English speaking readers can both understand the deep meaning of the translated text and can also pronounce the original Japanese words. Shinto is an ancient spiritual tradition, primarily practiced in Japan, which is now spreading its traditions to the western world. Its primordial rituals and traditions touch a deep chord within one's spiritual self. Shinto's focus on divinity of all beings and of all creation, on living with gratitude and humility, and on purification and lustration of one's self and environment will bring light and joy to any reader. This book of prayers will introduce the western reader to the deep spirituality of Shinto, providing explanation of the spiritual tradition and practice and providing a collection of 22 prayers for use in personal meditation and devotions.
Keywords: Shinto,Theological anthropology; Controversial literature,Shinto